Dynamics of Macrophage, T and B Cell Infiltration Within Pulmonary Granulomas Induced by Mycobacterium tuberculosis in Two Non-Human Primate Models of Aerosol Infection - Hunter, Laura; Hingley-Wilson, Suzie; Stewart, Graham R.; Sharpe, Sally A.; Salguero, Francisco Javier (Frontiers in Immunology, 2022)
Non-human primate models of Tuberculosis (TB) are one of the most commonly used within the experimental TB field because they closely mimic the whole spectrum of disease progression of human TB. However, the early cellular interactions of the pulmonary granuloma are still not well understood. The use of this model allows investigation into the early interactions of cells within pulmonary granulomas which cannot be undertaken in human samples. Pulmonary granulomas from rhesus and cynomolgus macaques from two timepoints post infection were categorised into categories 1 – 6 (early to late stage granulomas) and immunohistochemistry was used to identify CD68+ macrophages, CD3+ T cells and CD20+ B cells. Multinucleated giant cells and acid-fast bacilli were also quantified. At week four post infection, cynomolgus macaques were found to have more CD68+ cells than rhesus in all but category 1 granulomas. Cynomolgus also had a significantly higher percentage of CD20+ B cells in category 1 granulomas. At week twelve post infection, CD68+ cells were most abundant in category 4 and 5 granulomas in both species; however, there were no significant differences between them. CD3+ T cells and CD20+ B cells were significantly higher in the majority of granuloma categories in cynomolgus compared to rhesus. Multinucleated giant cells and acid-fast bacilli were most abundant in categories 5 and 6 at week 12 post challenge in both species. This study has identified the basic cellular composition and spatial distribution of immune cells within pulmonary granulomas in both rhesus and cynomolgus macaques over time. The data from this study will add to the knowledge already gained in this field and may inform future research on vaccines and therapeutics for TB.